2016
DOI: 10.1016/j.jmp.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A statistical test of the equality of latent orders

Abstract: 6It is sometimes the case that a theory proposes that the population means on two variables should have the same rank order across a set of experimental conditions. This paper presents a test of this hypothesis. The test statistic is based on the coupled monotonic regression algorithm developed by the authors. The significance of the test statistic is determined by comparison to an empirical distribution specific to each case, obtained via non-parametric or semi-parametric bootstrap. We present an analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 17 publications
(25 reference statements)
4
66
0
Order By: Relevance
“…Rips found that valid-unbelievable arguments received higher deduction endorsements than invalid-believable arguments, but this pattern was reversed for induction judgments. However, applied statetrace analysis to these data (see Dunn & Kalish, 2018), which involved plotting induction endorsement rates against deduction endorsement rates, and examining the fit of a model that assumes a single latent variable and thus a monotonic relationship (using an appropriate conjoint monotonic regression [CMR] procedure; Kalish, Dunn, Burdakov, & Sysoev, 2016).…”
Section: Tests Of the Simplest Single-process Model Using State-tracementioning
confidence: 99%
“…Rips found that valid-unbelievable arguments received higher deduction endorsements than invalid-believable arguments, but this pattern was reversed for induction judgments. However, applied statetrace analysis to these data (see Dunn & Kalish, 2018), which involved plotting induction endorsement rates against deduction endorsement rates, and examining the fit of a model that assumes a single latent variable and thus a monotonic relationship (using an appropriate conjoint monotonic regression [CMR] procedure; Kalish, Dunn, Burdakov, & Sysoev, 2016).…”
Section: Tests Of the Simplest Single-process Model Using State-tracementioning
confidence: 99%
“…This, like in the PAV algorithm, assumes merging the corresponding adjacent blocks, which explains why we call our algorithm SPAV (smoothed pool-adjacent-violators). The merging is associated with updating the coefficients that define the linear system (7). The corresponding number of arithmetic operations is proportional to the number of new active constraints.…”
Section: Smoothed Pool-adjacent-violators Algorithmmentioning
confidence: 99%
“…In order not to separately consider k = 0 as a special case, we introduce artificial μ 0 = 0 and constant-valued function y 0 (y k ). This does not change the relations established by (7). The equations of this linear system that correspond to j ∈ [k + 1, k − 1] can be represented in the form of the following recursive relation…”
Section: Lemma 42mentioning
confidence: 99%
See 1 more Smart Citation
“…Such applications can be found in psychology, biology, signal processing, economics and many other disciplines [1,2,21,22]. Perhaps the most widely known approach which allows for extracting a monotonic dependence is monotonic regression (MR) [5,38].…”
Section: Introductionmentioning
confidence: 99%